Food System Outcomes: An Overview and the Contribution to Food Systems Transformation - Stefanovic, Lilliana; Freytag-Leyer, Barbara; Kahl, Johannes (Frontiers in Sustainable Food Systems, 2020)
The interest in food system discourse has been increasing over time, however, the understanding of what makes a food system is still subject to variations depending on the research focus. While the earlier discourse was mainly value chain centered, the recent years have witnessed a shift in focus toward a more holistic view embracing the complex character of food systems. An indispensable component of the food systems approach are the food system outcomes that represent the results, or consequences, of the food system activities. This mini-review is based on a systematic literature review of food system outcomes and aims to provide an overview of the different discourses underpinning the food system outcomes while outlining the ones with a potential contribution to the transformation toward sustainable food systems. The variety of discourses spans from food (and nutrition) security and global environmental change to resilience and food system sustainability, potential performance assessments and metrics and, finally, the food systems transformation. Important outcomes within each of the discourses are highlighted and certain existing gaps are pointed out. While all discourses are essential for the overall understanding of the outcomes, these are certain commonalities in the discourses that bear synergetic potential for facilitating the transition to sustainable food systems.